2008
DOI: 10.1529/biophysj.108.131375
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Cell-to-Cell Connections Mediated by Nanotubular Structures

Abstract: Communication between cells is crucial for proper functioning of multicellular organisms. The recently discovered membranous tubes, named tunneling nanotubes, that directly bridge neighboring cells may offer a very specific and effective way of intercellular communication. Our experiments on RT4 and T24 urothelial cell lines show that nanotubes that bridge neighboring cells can be divided into two types. The nanotubes of type I are shorter and more dynamic than those of type II, and they contain actin filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
167
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(178 citation statements)
references
References 37 publications
11
167
0
Order By: Relevance
“…The results of some recent studies indicate that in many cases, vesicular transport between cells and between cell organelles over longer distances is not random, and that it takes place between specific surface regions of the cell organelles [6][7][8][9]. Such organized transport may be achieved via nanotubedirected transport involving carrier vesicles, or via direct transport through nanotubes.…”
Section: Membrane Nanotubesmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of some recent studies indicate that in many cases, vesicular transport between cells and between cell organelles over longer distances is not random, and that it takes place between specific surface regions of the cell organelles [6][7][8][9]. Such organized transport may be achieved via nanotubedirected transport involving carrier vesicles, or via direct transport through nanotubes.…”
Section: Membrane Nanotubesmentioning
confidence: 99%
“…They are versatile in ultra-structure and formation, and consequently also in function [reviewed in [50][51][52][53]. Our recent results revealed that the nanotubes in epithelial cells can be divided into two distinct types with respect to their formation, stability and cytoskeletal content [9]. Type I nanotubes are shorter, usually not longer than 30 μm, are more dynamic, and contain actin filaments.…”
Section: Membrane Nanotubesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanotubular structures are quite common in biological systems, in particular for establishing cell-to-cell connections 4 . Intercellular nanotubes (ICNs) formed from filopodial structures or after separation of tight cell-cell contacts mediate transport processes between cells.…”
Section: Introductionmentioning
confidence: 99%